Assessment of Chinese rehabilitation assistance system for disabled children - Gu, Zhongyuan; Tan, Hong; Zhang, Haomiao; Zhou, Rong (Frontiers in Public Health, 2023)
Using the social support theory for reference, a subject-object influencing mechanism model of China's rehabilitation assistance system for disabled children is built based on the survey data on 1,698 disabled children in 243 designated rehabilitation institutions in Hu'nan Province as well as the topic of the assessment and optimization of the rehabilitation assistance system for disabled children. The analysis using the structural equation modeling reveals that the inclusive welfare effect of the rehabilitation assistance system for disabled children has emerged, and disabled children receiving free rehabilitation in the designated institutions have achieved good rehabilitation results as a whole, however, disabled children of different age groups have generational differences in the rehabilitation effects, and the preferential aspect of the system needs to be strengthened. Government support, institutional support, and social support have positive non-equilibrium effects in enhancing the rehabilitation effects of disabled children. Institutional support plays a partial mediating role between government support, family support, and disabled children's rehabilitation effects, showing that the current social support system for the rehabilitation assistance of disabled children is experiencing structural, social and kernel changes, to evolve from the traditional closed and disconnected one-way resource support to open, coordinated, and interactive multi-support, and gradually become a comprehensive and efficient interactive support system with families as the foundation, institutions as the main body, and the government as the core.